Incidence of Japanese Encephalitis among Acute Encephalitis Syndrome Cases in West Bengal, India. (11th November 2013) - Bandyopadhyay, Bhaswati; Bhattacharyya, Indrani; Adhikary, Srima; Mondal, Saiantani; Konar, Jayashree; Dawar, Nidhi; Biswas, Asit; Bhattacharya, Nemai
Abstract : Background and Objectives . Japanese encephalitis (JE) is the most important cause of acute and epidemic viral encephalitis. Every year sporadic JE cases are reported from the various districts of West Bengal, indicating its endemicity in this state. JE vaccination programme has been undertaken by the State Health Department of West Bengal. This study was aimed at seeing the present scenario of JE among acute encephalitis syndrome (AES) cases in West Bengal. Materials and Methods . Blood and/or CSF samples were referred from suspected AES cases to the referral virology laboratory of the Calcutta School of Tropical Medicine from different hospitals of Kolkata. IgM antibody capture ELISA was performed on the CSF and serum samples by JE virus MAC ELISA kit supplied by the National Institute of Virology, Pune. Results . The present study reveals that 22.76% and 5% of the AES cases were positive for JE IgM in 2011 and 2012, respectively. JE is mainly prevalent in children and adolescents below 20 years of age with no gender predilection. Although the percentages of JE positive cases were high in 2011, it sharply decreased thereafter possibly due to better awareness programs, due to mass vaccination, or simply due to natural epidemiological niche periodicity due to herd immunity.